Health seeking behavior among women in Bhimtar, Sindhupalchowk district of Nepal - Shrestha, Marina V.; Paudel, Leela; Pant, Smriti; Neupane, Samikchya; Manandhar, Naresh (International Journal Of Community Medicine And Public Health, 2017)
Background: When assessing and monitoring the health of a population, it is important to describe not only classical mortality and morbidity indicators but also, perceived illness, visits to primary health services, and utilization of the healthcare services provided. Objectives of the study were to determine the health status and factors affecting health seeking behaviour of women. Methods: A descriptive study was done at Bhimtar, Sindhupalchowk District in Nepal, involving 147 subjects sampled by purposive sampling. Study population consisted of women. Data was collected by house to house interview with pretested questionnaire during month of September 2016. Data was entered and then analysed using Statistical Package for the Social Sciences (SPSS) 20. Simple measures of statistics like frequency, percentages, means were used to represent the data in tables as a part of descriptive analysis and chi-square test was applied to see the association with dependent variables. Results: Among 80.9% women who had gynaecological problems, the highest prevalence rate of the disease was low back pain (60.5%) followed by lower abdominal pain (35.2%), dysmenorrhea (27.3%) and menstrual irregularities (27.3%). The first approach of seeking health for the reported illness among women was the traditional healer (51%). Regarding attitude towards modern medicine, 47.6% respondents replied that facilities were not available locally. Similarly regarding hindering factors for not utilizing health services, lack of female doctors (43.75%) and far distance of health care centre (37.5%) were the most common ones. Conclusions:Higher percentage of women in Bhimtar sought after the traditional healer as the best way for utilizing health services. Modern health care utilization was less because of the distance to be covered during illness and lack of doctors in the health centre.